Influence of glass basicity on redox interactions of iron-manganese-copper ion pairs in soda-lime-silica glass - Thiemsorn W. (2014)
The redox interactions of iron, manganese, and copper ion pairs including absorption characteristics in a multicomponent soda-lime-silica glass, were investigated. Glasses containing 11-19 mol % Na2O were melted under an air atmosphere in an electric furnace at 1450°C for 8 h. The results of chemical analysis indicated that the redox pairs of Fe2+/Fe 3+, Mn2+/Mn3+, and Cu+/Cu 2+ shift to more oxidized states as a function of increasing glass basicity. The redox interactions of individual pairs, e.g., Fe 2+/Fe3+-Mn2+/Mn3+, Fe 2+/Fe3+-Cu+/Cu2+, and Mn 2+/Mn3+-Cu+/Cu2+, were not strong but changed with glass basicity. For the three redox pairs, Fe 2+/Fe3+-Mn2+/Mn3+-Cu +/Cu2+, both Mn3+ and Cu2+ ions simultaneously and proportionally oxidized Fe2+ to Fe3+ and did not affect one another. The reaction constants log Q 2 of Fe2+/Fe3+-Mn2+/Mn3+ and Mn 2+/Mn3+-Cu+/Cu2+ redox pairs decreased while the Fe2+/Fe3+-Cu+/Cu 2+ and three redox pairs systems changed markedly with increasing the glass basicity. The oxidizing and reducing powers of each ion changed only slightly in the present of one another, and the absorption spectra of all the single polyvalent elements confirmed to the Lambert-Beer law. The spectra depended directly on the concentrations of each absorbing ion. While the spectra of glass doped with more than one element confirmed the direction of the equilibrium shift, they were used only to predict the degree of interaction. These investigations gave consistent results. © 2008 MAIK Nauka.